INDUKSI KALUS KRISAN (Chrysanthemum morifolium) DENGAN PENAMBAHAN BERBAGAI KOMBINASI PIKLORAM DAN BAP - Farikha, Sabrina Nur; Habibah, Noor Aini (JURNAL AGROTROPIKA, 2025)
Chrysanthemum (Chrysanthemum morifolium) contains secondary metabolites that are used as anticancer, anti-inflamantory, antioxidant, and antibiotic agents. In vitro techniques or tissue culture are considered capable of producing metabolites through callus culture with the addition of growth regulators (GRs). The objective of this study was to analyzed the effect of the type and concentration of Picloram and BAP on the formation of chrysanthemum callus. This study used a Completely Randomized Design (CRD) with two factors: treatment, consisting of the type of PGR (Picloram and BAP), and concentration, consisting of four treatment levels: 0 ppm, 1 ppm, 2 ppm, and 3 ppm. Quantitative data, including growth time, percentage, fresh weight and dry weight of callus, were analyzed using IBM SPSS Statistic 27, while qualitative data, including color and texture morphology of callus, were analyzed descriptively. The result show that Picloram has a significant effect on all observed parameters. The addition of BAP only affect the fresh weight of the callus, while the combination of Picloram and BAP affect both the fresh and dry weight of the callus. A Picloram concentration of 3 ppm was the most optimal treatment for all parameters, and the combination of 3 ppm Picloram + 3 ppm BAP produced the highest fresh and dry weights of the callus. The callus formed was predominantly yellowish-green in color with a crumbly texture. These findings indicate that the combination of 3 ppm Picloram + 3 ppm BAP is effective in increasing the efficiency of callus induction in C. morifolium.   Key words: BAP,callus, chrysanthemum, picloram